A case of IV degree on acute radiation dermatitis in China. (2017) - Shen, Zhen; Chen, Ya-hong; Chen, Yue; Chen, Yan; Lv, Zhe; Gao, Hai-cheng
Abstract: This report investigates the nursing procedure of a case of adjuvant therapy of rectal cancer on IV degree of acute radiation dermatitis patients in the penis and scrotum junction. The lesion degree gradually increased. Fixation of the dressing was difficult in the penis and scrotum junction. The concept of wet healing with new dressings was used in patient. The silver ion dressings were used in inhibiting infection, and the wound was covered by the rimmed foam dressings. When it comes to the shaping period, water gel transparent paste was applied instead to cover the wound. The patient was just into the surgical treatment in the wound healed after six days.